The Pavilion of the Soviet Union, day view (Benjamin New Co., Ltd.)
The Pavilion of the Soviet Union covers 175,000 square feet and shows the achievements of its peoples during the 50 years of progress. Its theme is "Everything in the name of Man, for the benefit of Man."